Egyptian blue pigment in East Mediterranean wall paintings: A study of the lifetime of its optical infrared emission. (6th June 2018) - Linn, R.; Comelli, D.; Valentini, G.; Mosca, S.; Nevin, A.
Abstract: This study presents advances in the application of laser‐based methods to image and measure the luminescence lifetime of historical wall paintings containing Egyptian blue. Samples from Tel Kabri, a major Canaanite palace dated to 18th C. BCE, from the Roman city of Caesarea Maritima, from the 4–5th C. Byzantine tomb in Lohamei HaGeta'ot, and from a 6th C. Byzantine church of Shivta have been studied using time‐resolved photoluminescence spectroscopy and imaging. Taking into account the high sensitivity of the emission lifetime to the microenvironment surrounding the emitting species, here, we show for the first time that the optical emission from historical samples containing Egyptian blue particles exhibits meaningful lifetime variations. Indeed, the wall paintings from Tel Kabri, Lohamei HaGeta'ot, and Shivta present the shortest emission lifetime, close to 115–120 μs. However, samples from Caesarea Maritima wall paintings exhibit a different optical emission, which dumps more slowly with an average lifetime of 130 μs. Egyptian blue pigment particles, synthetised with modern methods, are associated with the longest emission lifetime of 147 μs. This study suggests that there is a possible link between the lifetime of the pigment's emission and its synthesis method.